Advanced glycation end products and their soluble receptor (sRAGE) in patients with Hashimoto’s thyroiditis on levothyroxine substitution - Csiha, Sára; Molnár, István; Halmi, Sándor; Hutkai, Dávid; Lőrincz, Hajnalka; Somodi, Sándor; Katkó, Mónika; Harangi, Mariann; Paragh, György; Nagy, Endre V.; Berta, Eszter; Bodor, Miklós (Frontiers in Endocrinology, 2023)
Background: Advanced glycation end products (AGEs) are heterogenous group of irreversible chemical moieties originated from non-enzymatic glycation and oxidation of proteins, nucleic acids, and lipids. The engagement of AGEs with their chief cellular receptor (RAGE) activates a myriad of signaling pathways contributing to the progression of chronic diseases like autoimmune thyroiditis, type 2 diabetes mellitus and its complications. Soluble RAGE (sRAGE) prevents AGE-RAGE interaction in a competitive manner. Objective: We investigated the association between serum AGE, sRAGE and thyroid function in 73 Hashimoto thyroiditis patients (HT) on levothyroxine substitution, and in 83 age, BMI and gender-matched healthy controls. Methods: The serum AGEs levels were determined by autofluorescence on a multi-mode microplate reader, and the serum sRAGE levels by ELISA method. Results: Mean AGE level was lower (10.71 vs 11.45 AU/µg protein; p=0.046), while mean sRAGE level was higher (923 vs 755 pg/mL; p<0.0005) in the serum of HT patients than the controls. AGE correlated with age, while sRAGE correlated negatively with BMI in both groups. We found negative correlation between AGE and fT3 levels (r=-0.32; p=0.006) and sRAGE and TSH levels (r=-0.27; p=0.022) in HT patients, while we failed to find association between AGE, sRAGE and parameters of thyroid function in the control group. Median AGE/sRAGE ratio was lower in HT patients than in controls (2.4, IQR 1.9 – 3.1 vs 3.3, IQR 2.3 – 4.1 AU/pg; p < 0.001). In HT patients, the AGE/sRAGE ratio correlated positively with BMI and correlated negatively with fT3. Conclusion: According to our results in HT patients lower TSH and higher fT3 levels within the reference range is accompanied by a favourable AGE/RAGE balance. Further investigations are needed to confirm these results.